CHARACTER EDUCATION IN MULTICULTURAL PERSPECTIVE: A LITERATURE REVIEW - Asep Saepurokhman; M. Makhrus Ali (Indonesian Journal of Education (INJOE), 2025)
This research aims to examine the importance and implementation of character education in a multicultural perspective through literature analysis. Multicultural character education focuses on teaching values that encourage respect for cultural, ethnic and religious diversity. The results of the literature review show that this education not only develops the cognitive aspects, but also the affective and social aspects of learners, in order to form individuals who are aware and sensitive to differences and able to interact harmoniously in a heterogeneous society. Challenges in its implementation, such as lack of understanding, awareness, resources and training, are obstacles that need to be overcome with supporting policies and ongoing training programmes. With a holistic approach and commitment from various parties, multicultural character education has great potential in forming a generation that is intelligent, empathetic, and able to coexist in a society full of diversity.